The Role of STSG and Delayed Midline Approximation In Abdominal Wall Reconstruction - Irwansyah, Denny; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
Acquired abdominal wall defects can result from previous surgery, trauma, infection and tumor resection. Complex abdominal wall defects challenge both general and plastic reconstructive surgeons. Skin grafting of abdominal viscera was originally described by Horton in 1953, demonstrated in dogs that STSG placed on the parietal peritoneum of abdominal viscera and buried in the peritoneal cavity would take well and survive. In 1994, Baker and Millard Jr reported serial cases of abdominal midline wound dehiscence which was treated with two stage abdominal wall reconstruction.Data was taken from medical and surgical records of patients consulted to the plastic surgery division with and acquired abdominal defect. We are reporting, Male, 42 yo, previous history of Perforated appendicitis with general peritonitis. We performed 2 stage reconstruction of abdominal wall for this patient.Treatment for an abdominal defect is selected on the basis of several factors, including the medical status of the patient, wound bed preparedness, depth, size and location of the defect. The goals of abdominal reconstruction are restoration of function and integrity of the musculo-fascial abdominal wall, prevention of visceral eventeration and provision of dynamic muscle support.Skin grafting and delayed midline approximation are one of the reconstructive option available and deserve to be considered in the high risk, septic patient without compromising the patient final reconstructive result.